Virological characterization of a new isolated strain of Andes virus involved in the recent person-to-person transmission outbreak reported in Argentina. - Rocio Coelho; Sebastian Kehl; Natalia Periolo; Emiliano Biondo; Daniel Alonso; Celeste Perez; Darío Fernández Do Porto; Gustavo Palacios; Alexis Edelstein; Carla Bellomo; Valeria Paula Martinez (PLoS Neglected Tropical Diseases)
On November 2, 2018, a person-to-person transmission outbreak of Andes virus (Orthohantavirus andesense) began in the small town of Epuyén, Argentina. The strain demonstrated a high capacity for sustained transmission among the human population requiring the implementation of quarantine measures, rigorous contact tracing, isolation of close contacts, and active clinical monitoring to prevent further spread. In this study, we report the isolation of this strain, which we name the ARG-Epuyén strain, directly from a clinical sample after just three passages in cell culture. Complete sequencing revealed only a single amino acid change post-isolation, suggesting that this strain can be considered a non-adapted wild-type Andes virus, marking a critical step toward the development of medical countermeasures against this emerging pathogen. The pathogenicity and transmissibility potential of ARG-Epuyén were evaluated in hamsters, the only animal model for Hantavirus Pulmonary Syndrome. Additionally, this strain was compared with Andes/ARG, an ANDV strain previously isolated from the same geographical area in the Argentinian Patagonia, from a rodent specimen. Our findings revealed high infectiousness and efficient hamster-to-hamster transmission through direct contact experiments, although ARG-Epuyén appeared to be less pathogenic than Andes/ARG.